ANALYSIS OF RISK, EFFECTIVENESS AND QUALITY ASSESSMENT OF THE USE OF OUTSOURCING SERVICES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Ergasheva , Nasiba (Innovatsion texnologiyalar, 2024)
The problem of evaluating the risk, efficiency and quality of use in preschool educational organizations, including the goals and tasks of outsourcing services, is one of the most urgent issues at the moment, because feeding, teaching and various activities of children aged 3-6 in preschool educational organizations Scientifically based proposals and recommendations are presented on the selection of the outsourcing services market by the client, the conclusion of the outsourcing contract and the management processes to reduce the level of risk and increase the efficiency and quality of services. The feasibility of using the AСTI (outsourcing, customer, third party and integrated) method of solving these problems has been developed. According to the research process, the use of AСTI method of assessing the risk, efficiency and quality of using outsourcing services in preschool educational organizations showed a decrease in the level of risk, an increase in quality and efficiency. By attracting the most competitive and efficient organizations of preschool education organizations in the relevant field of activity, the opportunity to use innovative technologies at a low cost was provided, the efficiency of using all resources and the possibility of reducing them was increased.